Respuesta de la palma africana (Elaeis guineensis Jacq.) bajo la aplicación de basacote, durante la etapa de pre vivero. - Rojas Chapín, Oswaldo Gabriel (2017)
The present investigation was carried out in the hacienda of Mr. Humberto Ferrin in association and financing with the Company "Oleorios SA" between April and July of 2017, whose objective was to evaluate the response of the African palm (Elaeis guineensis Jacq ) under the application of basacote, this is due to the little management that is given to the nurseries and the little knowledge about an optimal fertilization during this stage. To carry out this study employed a completely random design with three replications in a bifactorial arrangement of two substrates (Peat and Bio Compost) four fertilization (0.0, 3.0, 6.0 and 9.0g). The variables under study were: plant height, number of leaves, stem diameter, leaf length four one economic analysis treatment. The treatment that gave the best height of the plant was the dose two with 20.74 cm and the three with 19.54 cm was an effect between the doses and the substrates evaluated since several interactions between the variables were found, the Factor fertilizer dose showed higher significant (P ≤ 0.05) in plant height, number of leaves, stem diameter, leaf length and four equally for one substrate (peat) showed significance ( P ≤ 0.05) for plant height with values of 20.13 after 60 days of evaluation, we found differences in the number of functional leaves for dose number two (3g) with 3.20 functional leaves. Differences were found for the same dose in the variable stem diameter with values of 0.31 cm, likewise for leaf length four with averages of 22.74 cm at 75 days of evaluation, the best cost / benefit ratio was obtained by treating two a value of 1.79 and a profit of $ 68.75 surpassing mostly to other treatments under study.